Alternative Paths to Structural Adjustment in Uzbekistan in a Three-Gap Framework - Ranaweera, Thilak (World Bank, Washington, DC, 2014)
The author presents an internally consistent macroeconomic framework that could be used as a first step toward a more comprehensive, quantitative and qualitative assessment of the adjustment alternatives facing Uzbekistan. The three-gap framework focuses on the major imbalances of the economy for evaluating policy choices facing Uzbekistan. It emphasizes the domestic, and external factors that determine economic outcomes, and welfare. The author attempts to quantify two policy scenarios-gradual as against an accelerated policy implementation strategy. He finds that an aggressive adjustment policy would indeed improve most performance, and welfare indicators. Two major ingredients of such an aggressive adjustment strategy are the unification of the exchange rate, and implementation of current account convertibility in the balance of payments. The author also draws attention to the relative importance of external financing, and the sustainability of the balance of payments under alternative structural adjustment paths facing Uzbekistan.